Phase- and gender-specific, lifetime, and future costs of cancer: A retrospective population-based registry study. Issue 26 (2nd July 2021) - Bugge, Christoffer; Brustugun, Odd Terje; Sæther, Erik Magnus; Kristiansen, Ivar Sønbø
Abstract : Abstract: Valid estimates of cancer treatment costs are import for priority setting, but few studies have examined costs of multiple cancers in the same setting. We performed a retrospective population-based registry study to evaluate phase-specific (initial, continuing, and terminal phase) direct medical costs and lifetime costs for 13 cancers and all cancers combined in Norway. Mean monthly cancer attributable costs were estimated using nationwide activity data from all Norwegian hospitals. Mean lifetime costs were estimated by combining phase-specific monthly costs and survival times from the national cancer registry. Scenarios for future costs were developed from the lifetime costs and the expected number of new cancer cases toward 2034 estimated by NORDCAN. For all cancers combined, mean discounted per patient direct medical costs were Euros (EUR) 21, 808 in the initial 12 months, EUR 4347 in the subsequent continuing phase, and EUR 12, 085 in the terminal phase (last 12 months). Lifetime costs were higher for cancers with a 5-year relative survival between 50% and 70% (myeloma: EUR 89, 686, mouth/pharynx: EUR 66, 619, and non-Hodgkin lymphoma: EUR 65, 528). The scenario analyses indicate that future cancer costs are highly dependent on future cancer incidence, changes in death risk, and cancer-specific unit costs. Gender- and cancer-specific estimates of treatment costs are important for assessing equity of care and to better understand resource consumption associated with different cancers. Cancers with an intermediate prognosis (50%–70% 5-year relative survival) are associated with higher direct medical costs than those with relatively good or poor prognosis. Abstract : Supplemental Digital Content is available in the text